Acceptance of fetal movements recording in low risk pregnant women - Gómez, Luis (2015)
OBJETIVE: To compare the acceptability of two registers of fetal movements perceived by the mother in a low-risk population. Location: San Bartolome Hospital. MATERIALS AND METHODS: Between October 1998 and March 1999, 350 pregnant women randomly selected for recording fetal movements in the chart proposed by the Latin American Center for Perinatology (CLAP) and 350 for the record in an alternate graph ("Count up 10 "). The difficulty filling, the performance thereof was evaluated, and the degree of acceptance of both primers was compared. The results were subjected to statistical evaluation with x2 test, accepting a value of p <0.05 as significant. RESULTS: Of 700 pregnant women evaluated, 64% (n = 224) of the Primer Group CLAP aptly met the registration of fetal movements, compared with 91% (n = 319) group Primer "Count to 10" ( . p <0.01) CONCLUSION: For a low-risk pregnant population, Primer "Count to 10" ensures compliance with the registration of fetal movements.